Effect of shade on ecophysiology of cocoa under stress conditions - Mensah, E.O. (University of Ghana, 2021)
Climate models predict increasing air temperature and decreasing rainfall patterns among cocoa growing regions around the world. Both heat and drought stress are known to affect physiology of cocoa plants through reduced rates of photosynthesis, lack of water and generally impaired physiological processes. This in turn leads to decreased yields and in severe cases, increased risks of mortality. Many studies have reported positive effects of shade on cocoa production; however, interest of full sun cocoa farming has been increasing over the last 20 – 40 years due to higher yields under full sun conditions with higher inputs of fertilizer. However, most of the cocoa farms in Ghana are owned by small households who cannot afford to invest into more fertilizer applications. Therefore, providing shade to buffer cocoa against erratic climatic conditions could help sustain the cocoa industry while protecting the environment. Notwithstanding, a strong debate on whether shade can buffer physiological performances of cocoa against climate change thus exists. Reports have indicated shade limiting the effects of bad weather on cocoa, but few on-farm studies have so far been done in tropical conditions to back this claim. The aim of this research was therefore to study the effects of drought and elevated temperature on performances of cocoa as a tropical understory plant and to ascertain whether shade can modify the effects. The research was carried out in two separate experiments. In experiment one, the aim was to evaluate shade on cocoa plants under different levels of water suppression. The study was conducted in a farmer’s field with 12-year-old cocoa plants. Water suppression was achieved using plastic sheets to reduce through fall to between 33% and 66%. Shade was provided with 40% black shade net raised 6.5 m over the cocoa plants. Data taken covered a period of 33 months with parameters such as chlorophyll fluorescence, water potential, photosynthesis, stem expansion and yield were monitored. In experiment two, effects of heat on physiological performances of cocoa were studied using 6-month-old cocoa seedlings. Shade was provided using 60% black shade net while air temperature 2 to 4 oC above ambient was achieved using infra-red heaters. The experiment took place in September/October 2019 wet months and was repeated in the March/April 2020 dry months. Results from experiment one confirmed the hypothesis that drought can alter physiological functions of cocoa plants and shade can be a promising strategy to modify the effects. Drought had direct effect on water status in the plant affecting plant water potential, stem expansion, chlorophyll fluorescence and photosynthesis. Cocoa plants do not efficiently regulate their stomata to conserve water under drought conditions indicating the need for a constant supply of water to the plants. Canopy density, flower production, cherelles and pods count were higher under shade conditions, however, cherelles and pod damage were a significant problem under shade. Yield in kilograms per hectare depended on season, water availability or shade varying between 90 to 1100 kg/ha/season among treatments. Shade increased yield to about 1100 kg/ha/season irrespective of the levels of water suppression while water suppression proportionally reduced dry weight yield of cocoa plants whatever the shade levels. The 2/3 water suppression plots under full sun conditions had the least yield of 286 kg/ha/season compared with same treatment under shade conditions with yield average of 431 kg/ha/season. In experiment two, shade and heat had additive effects on growth, and physiological performances of cocoa at the seedlings level. However, interactive effects of shade and heat were observed on the immediate climatic conditions of the plants; an indication that shade can modify the immediate harsh conditions around the plants. Shade increased chlorophyll fluorescence, leaf area, chlorophyll pigments of leaves and reduced leaf damage. Shaded plants revealed maximum efficient utilization of limited light available by recording lower light saturation in the range of 325 – 380 μmol m-2 s-1 and light compensation between 0 – 6 μmol m-2 s-1. Full sun plants on the other hand gave slightly higher light saturation between 427 – 520 μmol m-2 s-1 while light compensation ranged between 11 – 18 μmol m-2 s-1. Also, full sun conditions increased leaf density and stomata per unit area and rate of photosynthesis. Heat further reduced light saturation points and increased light compensation points under shade and full sun conditions. Heat affected chlorophyll fluorescence reflecting damages to photosystem II light harvesting complexes, slowing the rate of photosynthesis. Plants responded to raised heat with increased concentration of heat shock proteins (HSPs), lower light saturation points, reduced growth in height and a shift of optimal temperature for photosynthesis to higher levels to acclimate to or avoid the heat stress. Shade thus, can minimize negative effects of drought and heat on cocoa to improve yield of the plant.